2004
DOI: 10.1080/14992020400050030
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus impairs cognitive efficiency

Abstract: Many people who complain of tinnitus say that the noises impair their mental concentration. This complaint was investigated by self-report (primarily the Cognitive Failures Questionnaire) and by means of five cognitive tasks, four presented via laptop computer and one given manually. The tasks measured performance under single- and dual-task conditions and included tests of sustained attention, reaction time, verbal fluency and immediate and delayed memory. Two groups of outpatients attending audiological clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
201
4
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(218 citation statements)
references
References 20 publications
11
201
4
2
Order By: Relevance
“…The results suggest that tinnitus affects performance on tasks requiring memory and/or attention. G. showed that selective attention, as measured by the Stroop color and word test (Stroop, 1935), was impaired among people with tinnitus; in addition, as reported by Hallam et al (2004), performance of a tinnitus group was slower than that of a nonclinical group on a dual task. The control of attentional processes underpins these phenomena and warrants closer investigation.…”
Section: Tinnitus and Cognitive Functionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results suggest that tinnitus affects performance on tasks requiring memory and/or attention. G. showed that selective attention, as measured by the Stroop color and word test (Stroop, 1935), was impaired among people with tinnitus; in addition, as reported by Hallam et al (2004), performance of a tinnitus group was slower than that of a nonclinical group on a dual task. The control of attentional processes underpins these phenomena and warrants closer investigation.…”
Section: Tinnitus and Cognitive Functionmentioning
confidence: 91%
“…It has been frequently noted that tinnitus is associated with reduced cognitive function (Gatehouse, 1991;Jacobson et al, 1996;Wilson, Henry, Bowen, & Haralambous, 1991), and some experimental research has appeared in the last 5 years that has confirmed effects of tinnitus on aspects of selective or divided attention and working or long-term memory (e.g., G. Andersson, Erickson, Lundh, & Lyttkens, 2000;G. Andersson, Ingerholt, & Jansson, 2003; G. Andersson, Khakpoor, & Lytkkens, 2002;Hallam, McKenna, & Shurlock, 2004). There is a need for the application of objective experimental methods, wherein tinnitus is manipulated as the independent variable, to assess the relationship between self-reported tinnitus and performance on cognitive tasks (the dependent variables).…”
Section: Tinnitus and Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of the distress experienced from the tinnitus is determined not by the acoustic characteristics, such as pitch and loudness of tinnitus (Andersson, 2003; Henry & Meikle, 2000; Hiller & Goebel, 2007), but by the cognitive, emotional and behavioural reactions to it (Andersson, 2002; Andersson & Westin, 2008; Cima, Crombez, & Vlaeyen, 2011; McKenna, Handscomb, Hoare, & Hall, 2014). Many tinnitus patients suffer from insomnia (Cronlein et al, 2016), concentration difficulties (Hallam, McKenna, & Shurlock, 2004; Rossiter, Stevens, & Walker, 2006) or headaches (Langguth et al, 2015). Comorbid mental symptoms of anxiety, depression and post-traumatic stress are common (Fagelson, 2007; Hinton, Chhean, Pich, Hofmann, & Barlow, 2006; McCormack et al, 2015; Pattyn et al, 2016; Zoger, Svedlund, & Holgers, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as an auditory sound perception in the absence of a generated sound stimulus, occurring from a failure in the auditory system (central and/or peripheral), encompassing the auditory sound masking 1,2 . Tinnitus is related to a number of structures of the central nervous system, and to find out the role of each of these structures is one of the major challenges associated with treatment 3,4 .…”
Section: Introductionmentioning
confidence: 99%